Optimum Condition of Pullulanase Production by Liquid State and Solid State Fermentation (SSF) Method from Bacillus Licheniforms (BS18) - Khalaf, Amna; Aldeen, Sanaa (Iraqi Journal of Science, 2023)
Select 30 isolate from Bacillus to detect the ability to produce pullulanase enzyme in liquid and solid state fermentation, and use the isolate Bacillus licheniformis (Bs18) because the highest production of enzyme, the optimum condition for the production of enzyme by liquid state fermentation (LSF) in growen with: media contains starch + pullulan as a carbon source, peptone as a nitrogen source, inoculums size 2 ml, and incubated at 40 C° with pH 7 for 48 hrs. In addition pullulanase production by solid state fermentation (SSF) was investigated using isolated Bacillus licheniformis (Bs18). Optimization of process parameters were carried out ,the optimum solid substrate , Temperature , pH , incubation period , inoculation size , hydration solution and substrate to moisture ratio were found to be corn bran + rice bran (w/w) , 37°C , 6.0 , 48hr , 2ml , (0.2M) phosphate buffer , and 1:2 respectively. Calcium ions (2mM) enhanced enzyme activity by increasing its activity to 170%. Solid state fermentation had given higher production of pullulanase than liquid state fermentation (LSF).